Use of levosimendan in the treatment of cerebral vascular vasospasm: a case study - Onichimowski D; Nosek K; Goraj R; Jalali R; Wińska A; Pawlos A; Tuyakov B (Dove Medical Press, 2018)
Dariusz Onichimowski,1 Krzysztof Nosek,2 Radosław Goraj,1 Rakesh Jalali,3 Aleksandra Wińska,2 Aleksandra Pawlos,4 Bułat Tuyakov1 1Department of Anesthesiology and Intensive Care, School of Medicine, Collegium Medicum, University of Warmia and Mazury, Olsztyn, Poland; 2Department of Neurology, School of Medicine, Collegium Medicum, University of Warmia and Mazury, Olsztyn, Poland; 3Department of Emergency Medicine, School of Medicine, Collegium Medicum, University of Warmia and Mazury, Olsztyn, Poland; 4Department of Pharmacology and Toxicology, Center for Experimental Medicine, Faculty of Medical Sciences, University of Warmia and Mazury, Olsztyn, Poland Abstract: Despite the progress in the management of cerebral arterial aneurysms, subarachnoid hemorrhage (SAH) remains the major cause of neurological disability. While SAH-related deaths usually occur as a result of brain impairment due to hemorrhage, permanent neurological deficits are caused by cerebral ischemia due to edema and spasm of cerebral arteries. Additionally, ~20%–30% of patients with SAH develop secondary cardiomyopathy; this phenomenon is known as neurogenic stress cardiomyopathy (NSC), which is associated with increased mortality and poor long-term prognosis. Levosimendan is a new inotropic drug that causes calcium sensitization of troponin C, thus increasing contraction force of myofilaments. The drug also causes opening of ATP-dependent potassium channels in vascular smooth muscles, which results in dilatation of veins and arteries, including cerebral arteries. To date, there have been several reports of levosimendan application in patients with SAH and neurogenic stress cardiomyopathy, and the effect of the drug on vasospasm has been previously advocated. This paper presents a case report of a 57-year-old patient with massive SAH, where levosimendan was used for reducing vasospasm. Keywords: cerebral arterial aneurysm, subarachnoid hemorrhage, cerebral vasospasm, levosimendan